Concept of Caste and Class in India: A Theoretical Framework: Understanding the caste hierarchy in pre-modern India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Caste, the rural community, and the joint family have added to social and social solidarity in India, where contrasts of race and culture were probably going to incite ceaseless conflict. In spite of the fact that they make up an interwoven smaller and strong structure they are plastic, bowing to economic powers. Through the caste system the aboriginal clans have been bit by bit ingested into Hindu social association. As workers, craftsman’s, and brokers ascend in the economic scale, they rise likewise in caste, not as people but rather as groups. Relatively persistent are the procedures of separation and combination of castes and sub castes, particularly in the lower rungs of the Hindu social stepping stool. With the growth of urban areas and of industrial development caste has relinquished a significant number of its confinements and has shown its versatility to wind up noticeably the society or exchange union in the new system of industry. Classical examinations on pre-modern Indian social structure have recommended evident contrasts between the Indian caste system and social stratification as one can perceive in different parts of the world. Be that as it may, one needs to question such fanatical statements that such immense contrasts truly existed. An undertaking is made in this exploration concentrate to think about the nature of caste hierarchy in pre-modern India. The caste system forms the huge premise of pre-modern Indian social structure.